Age-Related Changes in Neuromodulatory Control of Bladder Micturition Contractions Originating in the Skin - Hotta, Harumi; Suzuki, Harue; Iimura, Kaori; Watanabe, Nobuhiro (Frontiers in Neuroscience, 2018)
The brainstem is essential for producing micturition contractions of the urinary bladder. Afferent input from perineal skin evoked by gentle mechanical stimulation inhibits micturition contractions by decreasing both ascending and descending transmissions between the brainstem and spinal cord. Dysfunction of this inhibitory mechanism may be one cause of the increase in the prevalence of overactive bladder in old age. The aim of this study was to examine effect of aging on function of skin afferent fibers that inhibit bladder micturition contractions in rats. We used anesthetized male rats in three different age groups: young adult (4–5 months old), middle aged (6–9 months old), and aged (27–30 months old). The bladder was expanded to produce isovolumetric rhythmic micturition contractions. Skin afferent fibers were activated for 1 min either by electrical stimulation (0.5 ms, 0.2–10 V, 0.1–10 Hz) of the cutaneous branch of the pudendal nerve or by gentle mechanical skin stimulation with an elastomer roller. When skin afferent nerves were activated electrically, micturition contractions were inhibited in a similar manner in all age groups, with long latency inhibition induced by excitation of Aβ fibers and short latency inhibition by additional Aδ and C fiber excitation (at 1–10 Hz). On the contrary, when skin afferent nerves were activated mechanically by rolling, latency of inhibition following rolling stimulation was prolonged in aged rats. Single unitary afferent nerve activity of low-threshold mechanoreceptors (LTMs) from the cutaneous nerve was recorded. The discharge rate during rolling was not significantly reduced in Aβ units but was much lower in Aδ and C units in aged rats (0.4 and 0.5 Hz, respectively) than in young adult rats (3 and 7 Hz). These results suggest that the neural mechanism that inhibits bladder micturition contractions by skin afferent input is well maintained in old age, but the early inhibition by gentle skin stimulation is decreased because of reduced responses of Aδ- and C-LTMs.